To solve for b, you need to isolate it on one side of the equation.
Starting with the equation:
39 = 28 - b
First, you can subtract 28 from both sides of the equation:
39 - 28 = 28 - b - 28
This simplifies to:
11 = -b
To solve for b, you need to isolate it. Since -b is the same as multiplying b by -1, you can multiply both sides of the equation by -1:
11(-1) = -b(-1)
This gives you:
-11 = b
Therefore, b is equal to -11.
Solve for bb.
39, equals, 28, minus, b
39=
28−b
11 answers
Solve.
8, left bracket, z, minus, 4, right bracket, equals, minus, 8
8(z−4)=
−8
8, left bracket, z, minus, 4, right bracket, equals, minus, 8
8(z−4)=
−8
To solve for z, you need to isolate it on one side of the equation.
Starting with the equation:
8(z - 4) = -8
First, you can distribute the 8 to both terms inside the parentheses:
8z - 32 = -8
Next, you can add 32 to both sides of the equation to isolate the term with z:
8z - 32 + 32 = -8 + 32
This simplifies to:
8z = 24
To solve for z, you can divide both sides of the equation by 8:
8z/8 = 24/8
This gives you:
z = 3
Therefore, z is equal to 3.
Starting with the equation:
8(z - 4) = -8
First, you can distribute the 8 to both terms inside the parentheses:
8z - 32 = -8
Next, you can add 32 to both sides of the equation to isolate the term with z:
8z - 32 + 32 = -8 + 32
This simplifies to:
8z = 24
To solve for z, you can divide both sides of the equation by 8:
8z/8 = 24/8
This gives you:
z = 3
Therefore, z is equal to 3.
Solve.
2, left bracket, 6, x, plus, 2, right bracket, equals, 40
2(6x+2)=
40
2, left bracket, 6, x, plus, 2, right bracket, equals, 40
2(6x+2)=
40
To solve for x, you need to isolate it on one side of the equation.
Starting with the equation:
2(6x + 2) = 40
First, you can distribute the 2 to both terms inside the parentheses:
12x + 4 = 40
Next, you can subtract 4 from both sides of the equation to isolate the term with x:
12x + 4 - 4 = 40 - 4
This simplifies to:
12x = 36
To solve for x, you can divide both sides of the equation by 12:
12x/12 = 36/12
This gives you:
x = 3
Therefore, x is equal to 3.
Starting with the equation:
2(6x + 2) = 40
First, you can distribute the 2 to both terms inside the parentheses:
12x + 4 = 40
Next, you can subtract 4 from both sides of the equation to isolate the term with x:
12x + 4 - 4 = 40 - 4
This simplifies to:
12x = 36
To solve for x, you can divide both sides of the equation by 12:
12x/12 = 36/12
This gives you:
x = 3
Therefore, x is equal to 3.
Solve for x.
3, left bracket, x, plus, 5, right bracket, plus, 3, x, plus, 1, equals, minus, 32
3(x+5)+3x+1=
−32
3, left bracket, x, plus, 5, right bracket, plus, 3, x, plus, 1, equals, minus, 32
3(x+5)+3x+1=
−32
To solve for x, you need to isolate it on one side of the equation.
Starting with the equation:
3(x + 5) + 3x + 1 = -32
First, you can distribute the 3 to both terms inside the first set of parentheses:
3x + 15 + 3x + 1 = -32
Next, you can combine like terms:
6x + 16 = -32
To isolate x, you can subtract 16 from both sides of the equation:
6x + 16 - 16 = -32 - 16
This simplifies to:
6x = -48
To solve for x, you can divide both sides of the equation by 6:
6x / 6 = -48 / 6
This gives you:
x = -8
Therefore, x is equal to -8.
Starting with the equation:
3(x + 5) + 3x + 1 = -32
First, you can distribute the 3 to both terms inside the first set of parentheses:
3x + 15 + 3x + 1 = -32
Next, you can combine like terms:
6x + 16 = -32
To isolate x, you can subtract 16 from both sides of the equation:
6x + 16 - 16 = -32 - 16
This simplifies to:
6x = -48
To solve for x, you can divide both sides of the equation by 6:
6x / 6 = -48 / 6
This gives you:
x = -8
Therefore, x is equal to -8.
Solve for x.
minus, 2, left bracket, x, plus, 3, right bracket, plus, 4, x, minus, 4, equals, minus, 14
−2(x+3)+4x−4=
−14
minus, 2, left bracket, x, plus, 3, right bracket, plus, 4, x, minus, 4, equals, minus, 14
−2(x+3)+4x−4=
−14
To solve for x, you need to isolate it on one side of the equation.
Starting with the equation:
-2(x + 3) + 4x - 4 = -14
First, you can distribute the -2 to both terms inside the first set of parentheses:
-2x - 6 + 4x - 4 = -14
Next, you can combine like terms:
2x - 10 = -14
To isolate x, you can add 10 to both sides of the equation:
2x - 10 + 10 = -14 + 10
This simplifies to:
2x = -4
To solve for x, you can divide both sides of the equation by 2:
2x / 2 = -4 / 2
This gives you:
x = -2
Therefore, x is equal to -2.
Starting with the equation:
-2(x + 3) + 4x - 4 = -14
First, you can distribute the -2 to both terms inside the first set of parentheses:
-2x - 6 + 4x - 4 = -14
Next, you can combine like terms:
2x - 10 = -14
To isolate x, you can add 10 to both sides of the equation:
2x - 10 + 10 = -14 + 10
This simplifies to:
2x = -4
To solve for x, you can divide both sides of the equation by 2:
2x / 2 = -4 / 2
This gives you:
x = -2
Therefore, x is equal to -2.
Solve for x in simplest form.
3, equals, start fraction, 3, divided by, 2, end fraction, left bracket, 7, x, plus, 10, right bracket
3=
2
3
(7x+10)
3, equals, start fraction, 3, divided by, 2, end fraction, left bracket, 7, x, plus, 10, right bracket
3=
2
3
(7x+10)
To solve for x, you need to isolate it on one side of the equation.
Starting with the equation:
3 = \frac{3}{2}(7x + 10)
To isolate x, you can multiply both sides of the equation by the reciprocal of \frac{3}{2}, which is \frac{2}{3}:
3 \cdot \frac{2}{3} = \frac{3}{2}(7x + 10) \cdot \frac{2}{3}
This simplifies to:
2 = \frac{7x + 10}{2}
To get rid of the fraction, you can multiply both sides of the equation by 2:
2 \cdot 2 = \frac{7x + 10}{2} \cdot 2
This gives you:
4 = 7x + 10
Next, you can subtract 10 from both sides of the equation:
4 - 10 = 7x + 10 - 10
This simplifies to:
-6 = 7x
To solve for x, you can divide both sides of the equation by 7:
\frac{-6}{7} = \frac{7x}{7}
This gives you:
-\frac{6}{7} = x
Therefore, x is equal to -\frac{6}{7} in simplest form.
Starting with the equation:
3 = \frac{3}{2}(7x + 10)
To isolate x, you can multiply both sides of the equation by the reciprocal of \frac{3}{2}, which is \frac{2}{3}:
3 \cdot \frac{2}{3} = \frac{3}{2}(7x + 10) \cdot \frac{2}{3}
This simplifies to:
2 = \frac{7x + 10}{2}
To get rid of the fraction, you can multiply both sides of the equation by 2:
2 \cdot 2 = \frac{7x + 10}{2} \cdot 2
This gives you:
4 = 7x + 10
Next, you can subtract 10 from both sides of the equation:
4 - 10 = 7x + 10 - 10
This simplifies to:
-6 = 7x
To solve for x, you can divide both sides of the equation by 7:
\frac{-6}{7} = \frac{7x}{7}
This gives you:
-\frac{6}{7} = x
Therefore, x is equal to -\frac{6}{7} in simplest form.